2016
DOI: 10.1021/acs.nanolett.6b04449
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Carrier Tunneling in van der Waals Heterostructures for Ultrahigh Detectivity

Abstract: Semiconducting transition metal dichalcogenides (TMDs) are promising materials for photodetection over a wide range of visible wavelengths. Photodetection is generally realized via a phototransistor, photoconductor, p-n junction photovoltaic device, and thermoelectric device. The photodetectivity, which is a primary parameter in photodetector design, is often limited by either low photoresponsivity or a high dark current in TMDs materials. Here, we demonstrated a highly sensitive photodetector with a MoS/h-BN/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
182
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(186 citation statements)
references
References 37 publications
4
182
0
Order By: Relevance
“…With the insulator acting as the tunneling layer, e.g. hexagonal boron nitride (h-BN), DT occurs at low voltage and the carriers are dominated by F-N tunneling 13 Jones, which is about 100-1000 times higher than those of previously reported MoS 2 -based devices [21]. All these reports found that the embedded h-BN barrier in vertical stacks can dramatically reduce dark current and increase detectivity for photodetector application.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…With the insulator acting as the tunneling layer, e.g. hexagonal boron nitride (h-BN), DT occurs at low voltage and the carriers are dominated by F-N tunneling 13 Jones, which is about 100-1000 times higher than those of previously reported MoS 2 -based devices [21]. All these reports found that the embedded h-BN barrier in vertical stacks can dramatically reduce dark current and increase detectivity for photodetector application.…”
Section: Resultsmentioning
confidence: 95%
“…We believe that optimization of quality of the 2D materials or insulator thickness may obtain short transit time of photogenerated carriers across the channel, enhancing the photoresponse characteristics eventually. Table 1 shows the photoresponse performance of heterojunction tunneling photodetectors, based on different 2D materials and tunneling mechanisms [20,21,23,[34][35][36][37]. In the reported photovoltaic-type devices, photo-induced electron-hole pairs are separated by the built-in electric field, while the carrier tunneling follows different mechanisms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The surface passivation of this two-dimensional material can be understood by the fact that there are no overhanging chemical bonds on the surface, so van der Waals interactions allow different materials to be superimposed without lattice mismatches. This makes it possible to construct van der Waals heterogeneous structures based on various two-dimensional materials or two-dimensional materials integrated with photon structures [15].…”
Section: Introductionmentioning
confidence: 99%